Desain Sistem Inventory Berbasis Website pada PT. Api Precision Cikarang - Bisri, Muawan; Andriati, Dea Andini; Saputra, Ade (KH. A. Wahab Hasbullah University, 2021)
Inventory is a very vital business stage, and this is because inventory is closely related to production targets and sales targets in a business line. This study aims to design a website-based inventory system at PT. Api Precision as a support for the process of inventory transaction activities. The data collection method used is by conducting observations, interviews, and literature studies related to the problem being studied. Furthermore, the analysis and design of an inventory system are carried out to be built using the PHP and MySQL programming languages. The method used in developing this system is the waterfall method. The result of this research is creating a website-based inventory system design at PT Api Precision Cikarang to be continued as a system that can be integrated with other information systems.